One-way transnational magnetic mass damper model for structural response control against dynamic loadings - Nurulashikin Bahaman; Sk Muiz Sk Abdul Razak; Azlan Adnan; Norrazman Zaiha Zainol; Norhaizura Yahya; Khairunnisa Muhamad; Ahmad Nurfaidhi Rizalman; Mazizah Ezdiani Mohamad; Nur Adibah Ayuni Abd Malek (2018)
Structural responses should be reduced to minimize the consequent structural damage caused by dynamic excitation. The one-way translational magnetic mass damper model is developed as a new type of damper for the purpose of structural response control. The damper utilizes the concept of repulsive force between magnets with same poles to create a magnetic force to stabilize or bring the structure back to its original position. The dynamic performance of the structure was tested using a harmonic shaking table. In this study, the three parameters used are excitation speeds: 2.5V (low), 6.0V (medium) and 8.5V (high); strength of magnets: weak (N35), medium (N45) and strong (N52); and the mass in the damper: 40 g, 101 g and 162 g. The correlations of the parameters towards the structural displacement are verified in the testing. The displacement is highly reduced up to 100% at the first level and 85.2% at the fifth level. The most optimum structural response control was attained when a strong magnetic strength and mass of 162 g are used. When tested with three excitation speeds; 2.5V, 6.0V and 8.5V, the damper with this setting provides the optimum damping effect towards the structure in terms of displacement.